Quantifying climate change and its impact on surface water in the Cherrat watershed in northwest Morocco using satellite imagery and GIS - Gramz Mohamed; Batchi Mouhcine; Ouiaboub Lahcen; Mettouchi Mehdi; El Bouziani Jamal; Azagane Moulay Hichame; El Abbassi Mariam (E3S Web of Conferences)
The water potential situation in Morocco has a particularity, especially with the specific context climatic characterised by the dominance of aridity in several parts of the country, of which the Cherrat watershed in the northwest of the central plateau, which requires the preservation of water resources. With this in mind, the aim of this research is to highlight the surface water situation, in particular using a cartographic approach, in order to provide decision-makers with a vision of the surface water situation in the target area and to help them take the necessary and appropriate measures for equitable management, focusing on water sustainability. The results obtained from the use of satellite images and their processing through a geographic information system (GIS) demonstrate that the surface area of water increased from 0.6 ha to 6 ha between 1999 and 2009, but decreased to 4 ha by 2019. By 2023, there will also be an astounding 55 ha increase.